Unveiling Ryanair holdings PLC's value: forecasting and valuation analysis - Martins, Gustavo Miguel Pestana (2023)
This Master’s Thesis aims to determine an appropriate valuation for Ryanair Holdings PLC, a European short-haul airline operating in a highly cyclical industry vulnerable to economic, energy, and geopolitical fluctuations. Ryanair has managed to navigate through the Covid-19 pandemic, during which air travel ceased, causing airlines to struggle with fixed costs amid revenue loss. Although European air traffic is rebounding, significant changes have unfolded, mostly pertaining to altering travel trends, consumer behaviors, and flight patterns. Ryanair is betting big on expansion for the following decade, and has agreed with Boeing a big contract of 300 new Boeing 737 Max-10. This deal not only aims to modernize their fleet but also to widen its reach, particularly targeting the less explored Eastern European market. However, this growth occurs within a severely constrained market capacity, as major airlines have also committed to substantial aircraft orders, straining Boeing and Airbus manufacturers' production capabilities. Our model and DCF analysis forecast a €21.72 share price for FY25, which implies an annualized shareholder return of 14.05%, leading us to recommend a "buy" strategy.